MULTI-HOP WIRELESS SENSOR NETWORKS FOR REMOTE MONITORING OF SOIL MOISTURE - Zakaria, Siti Zubaidah (Universiti Teknologi PETRONAS, 2016)
As we know, recent development of wireless sensor networks (WSN) technology initiates many research works but most of them are implemented in simulation and rarely been tested for real world application. Thus, this project is conducted to study the performance of multi-hop WSN and apply it for remote soil moisture monitoring application. The motivation of this project is driven by the limitations of conventional soil monitoring technique that are inflexible and requires expensive cost associated with installation and hiring of an expert agronomist. Therefore, it is believed that deployment of multi-hop WSN technology with remote monitoring feature can solve those limitations with minimal human intervention, lower cost and capability of providing real time monitoring of large data. In this project, Crossbow IRIS motes were used to build a working testbed of sensor nodes to monitor the surrounding humidity, surrounding temperature of the crops and soil moisture in the form of volumetric water content (%VWC).